THE ALIENATION OF THE INDIVIDUAL AND THE PROBLEM OF MORAL CHOICE IN JONATHAN COE'S NOVEL “THE CLOSED CIRCLE” - Aliyeva Leyla Astan (International Journal of Innovative Technologies in Social Science, 2025)
The investigation sheds light on the issues of alienation of the individual in the novel “The Closed Circle” by the modern English writer Jonathan Coe. At the same time, it examines the problem of moral choice raised in the novel. The author of the article comes to the conclusion that J. Coe solves the issues of choice and lack of choice in a Hamlet-like way. Hamlet’s tragedy lies in his search for truth, and the tragedy of the novel’s hero lies in the lack of a chance to make a choice. His indecision and doubtful thoughts are also related to the problems prevailing in society. The peculiar sense of guilt expressed on the basis of the image of Hamlet is characterized as a characteristic feature of the hero. Lack of choice creates a dead end in the hero’s life, a feeling of indecision, hesitation until the end does not leave him, and thus, any action resembles a closed circle. All the characters of the work face their own sins and the dilemma of choice, which is also related to the problem of moral choice raised by the writer.